Evaluating the effects of coffee consumption on the structure and function of the heart from multiple perspectives - Xiong-Bin Ma; Yan-Lin Lv; Lin Qian; Jing-Fen Yang; Qian Song; Yong-Ming Liu (Frontiers in Cardiovascular Medicine)
ObjectiveTo assess the causal relationship between coffee consumption and cardiac structure and function in elderly European populations using multiple genetic methodologies.MethodsLeveraging genome-wide association study (GWAS) data from elderly European populations, we conducted linkage disequilibrium score regression (LDSC), two-step Mendelian randomization (MR), and colocalization analyses to investigate genetic associations, causal relationships, and mediating effects among these factors. Robustness of findings was verified through comprehensive sensitivity analyses.ResultsLDSC regression analysis revealed positive genetic correlations between coffee consumption and cardiac parameters, excluding left ventricular (LV) ejection fraction and right ventricular (RV) ejection fraction. MR results demonstrated favorable associations between increased coffee consumption and cardiac parameters. After applying the Bonferroni adjustment to IVW analysis, as coffee consumption increased by each 1-cup/day, LV end-diastolic volume increased (β = 0.128; 95% CI: 0.043–0.212; P = 0.002), an increase in LV end-systolic volume (β = 0.143; 95% CI: 0.053–0.232; P = 0.001), an increase in RV end-diastolic volume (β = 0.200; 95% CI: 0.095–0.305; P < 0.001), and an increase in RV stroke volume (β = 0.209; 95% CI: 0.104–0.313; P < 0.001). Mediation analyses indicated that each 1-cup/day increase in coffee consumption significantly correlated with reduced diastolic blood pressure (DBP) and elevated body mass index (BMI). Notably, higher DBP exhibited inverse associations with ventricular systolic/diastolic functional parameters, whereas increased BMI demonstrated positive associations with these parameters, collectively mitigating age-related ventricular volume loss. No U-shaped associations were detected in linear MR frameworks. Colocalization analyses confirmed shared causal genetic variants between coffee intake and cardiac remodeling phenotypes.ConclusionsGenetically predicted coffee consumption may counteract age-associated ventricular volume loss in elderly Europeans through dual mediation pathways involving DBP reduction and BMI elevation. These structural adaptations suggest potential cardioprotective mechanisms against senile cardiac atrophy. Future studies should prioritize the integration of coffee consumption into cardiovascular risk assessment frameworks and develop personalized recommendations based on individual health profiles.